Digital Marketing Strategies for Enhancing Customer Engagement : Insights from Small and Medium Enterprises (SMEs) - Huda Salih Mahdi al-Ammash; Wijdan al-Sayegh; Safa al-Sarai (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study explores digital marketing strategies employed by Small and Medium Enterprises (SMEs) to enhance customer engagement in an increasingly competitive business environment. By leveraging tools such as social media, email marketing, content marketing, and search engine optimization (SEO), SMEs can establish stronger connections with their target audience. The research highlights key practices, including personalized communication, interactive content, and data-driven decision-making, which contribute to customer loyalty and retention. Furthermore, challenges faced by SMEs, such as limited budgets and technological expertise, are discussed alongside potential solutions. The findings provide actionable insights for SMEs to optimize their digital marketing efforts and foster long-term customer relationships.